2012
DOI: 10.1523/jneurosci.5367-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Is Important for the Manifestations of α-SynucleinopathyIn Vivo

Abstract: Accumulation of misfolded α-synuclein (αS) is mechanistically linked to neurodegeneration in Parkinson's disease (PD) and other α-synucleinopathies. However, how αS causes neurodegeneration is unresolved. Because cellular accumulation of misfolded proteins can lead to endoplasmic reticulum stress/unfolded protein response (ERS/UPR), chronic ERS could contribute to neurodegeneration in α-synucleinopathy. Using the A53T mutant human αS transgenic (A53TαS Tg) mouse model of α-synucleinopathy, we show that disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
300
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(311 citation statements)
references
References 57 publications
(106 reference statements)
11
300
0
Order By: Relevance
“…Prior studies have shown that Asyn localizes to Rab1 ϩ membranes, alters membrane trafficking, and modulates ER stress signaling (27,36). Given that WNV manipulates ER stress signaling (34,37,38), we hypothesized that Asyn expression modulates ER stress signaling following viral infection and that, in the absence of Asyn, ER stress signals are increased in support of WNV replication.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior studies have shown that Asyn localizes to Rab1 ϩ membranes, alters membrane trafficking, and modulates ER stress signaling (27,36). Given that WNV manipulates ER stress signaling (34,37,38), we hypothesized that Asyn expression modulates ER stress signaling following viral infection and that, in the absence of Asyn, ER stress signals are increased in support of WNV replication.…”
Section: Resultsmentioning
confidence: 98%
“…We found that virus-induced Asyn localized with viral envelope proteins and significantly increased the localization with Rab1 ϩ membranes. Previous work has shown that Asyn localization to Rab1 ϩ membranes alters membrane transport from the ER to the Golgi body, resulting in changes in ER stress signals and ER remodeling within the neuron (27,36). In general, positive-stranded RNA viruses are dependent on membrane remodeling to support viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 is a major ER chaperone protein 23 involved in the UPR, which is frequently altered in neurodegenerative diseases, 32 known to interact with Syn in the ER in stress conditions. 33,34 We provided evidence that the binding of extracellular Syns to GRP78 occurs at the cell surface and leads to its clustering in discrete membrane domains, possibly as a consequence of inhibition of its lateral movement along the plasma membrane, and of its decreased recycling. Alternatively, Syn might induce clustering of GRP78 at the cell surface through changes in membrane composition, curvature and integrity.…”
Section: Discussionmentioning
confidence: 94%
“…Understanding the pathways by which misfolded proteins cause neurodegeneration is essential for developing efficient treatments for neurodegenerative disorders. On the other hand, although targeting ER stress may be beneficial for patients with neurodegenerative disorders, new therapeutic agents must be carefully screened and tested in appropriate disease models to avoid possible adverse effects [5,21,22,34].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of phosphorylation of eIF2α protected the A53T α-synuclein over expressing cells from cell death, suggesting that ER stress response was shifting the balance towards apoptosis [33]. Recent studies further indicate that the accumulation of α-synuclein within ER leads to chronic ER stress conditions that contribute to neurodegeneration in PD and other alpha-synucleinopathies [34,35]. Similarly, evidences have indicated that protein products of genes mutated in PD, such as ubiquitin carboxyl-terminal esterase L1 (UCHL1), leucine-rich repeat kinase 2 (LRRK2), Parkinson protein 2 (Parkin), PTENinduced kinase 1 (PINK1) and DJ-1, play a role in regulating protein stability and ER stress response [22,31,32].…”
Section: Parkinson's Diseasementioning
confidence: 99%